Worker falls with impalement by a steel bar that results in a penetrating scrotal injury: a case report (Journal of Ideas in Health, 2025)
Background: Scrotal injuries constitute the great bulk of genito-urinary traumas. Penetrating scrotal injuries are infrequent when compared to blunts. Moreover, impalement injuries by hard metals are rarer, especially when no permanent harm is left. Case presentation: A 38-year-old male construction site worker was brought to the accident and emergency (A&E) department after falling from a 3 meters-high building. On arrival, his look was horrific, as a large steel bar was penetrating his right chest causing pneumothorax. A second bar penetrated his scrotum from bottom to up. The patient was frightened by the accident. Vitals were normal, with no signs of major blood loss. The chest trauma was dealt with by the relevant team, while the scrotal injury necessitated emergency surgery. Operatively, the steel bar was found to travel miraculously across the scrotal contents sparing vital structures. Subsequently, the bar was removed leaving no permanent damage. The patient was discharged home uneventfully.Conclusion: A steel bar might cause an eerily external genital injury that passes throughout the scrotum without notable content damage.
Keywords: Male External Genital Injury, Penetration Scrotal Trauma, Acute Scrotum, Sharp Genital Trauma, Occupational Hazard, Fall with Impalement, Saudia Arabia